2021
DOI: 10.1101/2021.04.02.438214
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altered metal distribution in thesr45-1Arabidopsis mutant causes developmental defects

Abstract: The plant SR (serine/arginine-rich) splicing factor SR45 plays important roles in several biological processes, such as splicing, DNA methylation, innate immunity, glucose regulation and ABA signaling. A homozygous Arabidopsis sr45-1 null mutant is viable, but exhibits diverse phenotypic alterations, including delayed root development, late flowering, shorter siliques with fewer seeds, narrower leaves and petals, and unusual numbers of floral organs. Here, we report that the sr45-1 mutant presents an unexpecte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…The characterization of FIT NBs as speckles is interesting because regulation of splicing and epigenetic regulation is associated with iron deficiency gene expression. Genes were spliced incorrectly in a sr45-1 null mutant Arabidopsis line, and gene expression of FIT and FIT target genes was increased in sr45-1 seedlings, showing that an interplay between SR45 and the iron uptake machinery exists (Fanara et al, 2022). Alternative splicing was detected for FIT targets and the BHLH subgroup Ib genes in iron-deficient versus iron-sufficient conditions (Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The characterization of FIT NBs as speckles is interesting because regulation of splicing and epigenetic regulation is associated with iron deficiency gene expression. Genes were spliced incorrectly in a sr45-1 null mutant Arabidopsis line, and gene expression of FIT and FIT target genes was increased in sr45-1 seedlings, showing that an interplay between SR45 and the iron uptake machinery exists (Fanara et al, 2022). Alternative splicing was detected for FIT targets and the BHLH subgroup Ib genes in iron-deficient versus iron-sufficient conditions (Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This included the speckle components ARGININE/SERINE-RICH45-mRFP (SR45) and the serine/arginine-rich matrix protein SRm102-mRFP (Figure 5). SR45 is involved in splicing and alternative splicing and is part of the spliceosome in speckles (Ali et al, 2003), and was recently found to be involved in splicing of iron homeostasis genes (Fanara et al, 2022). SRm102 is a speckle component (Kim et al, 2016).…”
Section: Figure S3mentioning
confidence: 99%
See 1 more Smart Citation